Perceived benefits of pet ownership by middle-aged people with type 2 Diabetes mellitus - Hugues H., Beatriz (2016)
The study was conducted to explore the perception of people of middle-age with Type 2 Diabetes Mellitus (DM2) regarding ownership of companion animals and their relationship with personal satisfaction, benefits on mental health and metabolic control, and to the motivation on practicing physical activities. The study was descriptive, crosssectional, with 85 people from 49 to 58 years of age who had DM2, and were residents of Havana, Cuba. A self-administered questionnaire for assessing these aspects and obtaining demographic data was constructed. The results showed that 82% of the people felt very satisfied to share their lives with companion animals, 84% perceived a very beneficial relationship for their mental health, and 98% admitted that they were motivated to take better care of DM2. Also, within the 43 people who have dogs, 65% felt motivated to perform physical activities with their animals (long walks).